Characterization of UHMWPE/wood composites produced via dry‐blending and compression molding. Issue 4 (8th March 2013) - Mahfoudh, A.; Cloutier, A.; Rodrigue, D.
Abstract In this study, composites made from wood flour and ultra‐high molecular weight polyethylene (UHMWPE) were produced and characterized. In particular, the composites were initially prepared using a simple dry mixing technique and then compression molded. The effect of wood content on the mechanical properties was determined up to 30wt%. Characterization included scanning electron microscopy to investigate wood dispersion and interfacial bonding quality, while the mechanical tests included tensile, torsion, and flexion. The results show that good dispersion and adhesion was achieved and wood flour addition increased substantially (up to 97%) all the moduli in the range of conditions tested. Finally, it was found that hardness increased by about 5 Shore D points by adding 30% wood flour in UHMWPE. POLYM. COMPOS., 2013. © 2013 Society of Plastics Engineers